Risks of using psilocybin in treatment of treatment-resistant depression - Orzechowski, Michał; Orzechowska, Joanna; Fijałek, Paulina; Karczmarz, Jan; Paprocka, Aleksandra; Gutowska, Marika; Kosińska, Agnieszka; Świrk, Urszula; Belcarz, Wiktoria; Kalinowska, Karolina (Journal of Education, Health and Sport, 2025)
Introduction As depression rates continue to rise globally, the need for more effective and innovative treatments has become increasingly urgent, highlighting the potential impact of psilocybin as a promising therapeutic option. However, to ensure its safe and effective integration into clinical practice, it is essential to establish robust safety parameters for its administration. This paper focuses on addressing the risks associated with psilocybin therapy. We believe this paper can help understand risks as a platform for safety based treatment. Material and Methods A comprehensive literature search was conducted using the PubMed and Google Scholar databases, supplemented by references cited in the initially identified articles. The search focused on studies and reviews addressing the challenges and risks associated with psilocybin use in the treatment of treatment-resistant depression (TRD).